Mentoring Kolaborasi Instruktur Klinik Berhubungan dengan Persepsi terhadap Pendidikan Interprofesi - Priyandaru, Bayu Aji; Mulyono, Wastu Adi; Setiyani, Rahmi (Jurnal Keperawatan Soedirman, 2016)
Interprofessional collaboration is required to optimize health care. Interprofessional Education (IPE) is one of the strategies to prepare the collaboration skill since at educational stage. The implementation of IPE in the clinical setting can be conducted through the implementation of mentoring collaboration by CI. This study is to examine the relationship between perception of IPE and implementation of mentoring collaboration among Clinical Instructors (CI) in Banyumas Hospital. A cross-sectional study invited total of 175 CI’s to participate. Interdisciplinary Education Perception Scale (IEPS), and the modified Clinical Instructor Behavior Instrument (CIBI) were administered to measure the perception and the mentoring collaboration respectively. Results showed the majority of diploma degree in nursing (65.1 %) and over three years (77.0 %) experience as CI. Female CI population was slightly higher than the male (56.3 % compared to 43.7 %). The average score of CI’s perception of IPE was 83.63 %. Meanwhile, the average score of implementation of mentoring collaboration was 81.83 %. There was a significant relationship between perception of IPE and mentoring collaboration among CIs (p = 0.000 and r= 0.313). It concluded that there was a relationship between perception of IPE and the implementation of mentoring collaboration by CIs in Banyumas Hospital